Association of IL33 and IL1RAP Polymorphisms With Acute Anterior Uveitis - Huang, X.-F.; Chi, W.; Lin, D.; Dai, M.-L.; Wang, Y.-L.; Yang, Y.-M.; Jin, Z.-B.; Wang, Y. (Current Molecular Medicine, 2017)
Background: AAU (acute anterior uveitis) is the most common entity of uveitis characterized by acute vision loss and violent sore eyes. IL-33 and IL-1RacP have been found to play crucial roles in the innate immune system. Objective: In the present study, we investigated the association of IL33 and IL1RAP genes with AAU. Method: A total of 549 AAU patients and 1080 unrelated healthy controls were recruited for this study. Ten single nucleotide polymorphisms (SNPs) were genotyped using Sequenom Mass ARRAY technology. Results: Our findings demonstrated that IL1RAP-rs3773978 significantly associated with AAU and could serve as a genetic risk marker in Chinese AAU patients. A significantly increased frequency of the A allele and AA homozygosity of IL1RAP-rs3773978 was observed in AAU patients compared with that in controls (p=0.001, pc=0.01, OR=1.282, 95% CI 1.106 to 1.487; p=0.0003, pc=0.003, OR=1.647, 95% CI 1.255 to 2.163, respectively). Further stratification analyses showed that the genetic correlation may differ depending on HLA-B27 status, AS (ankylosing spondylitis) status, attack times and laterality status. Conclusion: Our findings provide new insights that enhance the current knowledge of uveitis genetics by demonstrating the specific functional roles of IL1RAP and other IL-1 family genes in uveitis.
Keywords: acute anterior uveitis